Peningkatan literasi bahasa inggris masyarakat Desa Wisata Kandri melalui pelatihan penerjemahan papan edukasi dan informasi - Alfin Rosyidha; Naila Rohmah; Eka Nur Salsabila; Nabila Amelia Agatha; Nabyla Rizky Putri Handayani; Assita Hilda Putri Assiva; Nabila Dzikria; Toufy Schendikia Sholekhah (Tintamas: Jurnal Pengabdian Indonesia Emas, 2026)
The community service aimed to enhance the English literacy of the Community-Based Tourism Group in Kandri Tourism Village by training them to translate local educational and informational boards into English. The limited availability of bilingual information had previously hindered international visitors from understanding the village’s educational value, historical background, and cultural potential. The program was implemented in several stages, including socialization, intensive training on basic translation concepts, tourism translation principles, cultural adaptation techniques, and hands-on practice translating 14 educational boards across the village. Participants received mentoring and editing support to ensure accuracy, naturalness, and contextual appropriateness of the translations for international tourism contexts. The results demonstrated significant improvements in participants’ skills, with meaning comprehension increasing by 32%, lexical accuracy by 28%, and the ability to produce informative translations by 35% based on pretest and posttest comparisons. The main outputs included a Translation Training Module and finalized translations developed for a Bilingual Tourism Booklet for Kandri Village, which contribute to strengthening the community and Tourism Awareness Group (Pokdarwis) capacity and improving the accessibility and quality of tourist information for international visitors.